URGENSI KECERDASAN SPIRITUAL DAN EMOSIONAL GURU DALAM PENDIDIKAN KARAKTER SISWA DI SEKOLAH - M. I. Suhifatullah (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Education in schools is not only an activity to develop aspects of students' intellectual intelligence, but also to develop various aspects of intelligence. This is in line with the Vision of the Ministry of National Education (now the Ministry of Education and Culture) 2025, namely "Producing Smart and Competitive Indonesian Personnel (Insan Kamil/Insan Plenary)". This means that it includes various intelligences or multiple intelligences which include spiritual intelligence, emotional intelligence, social intelligence, intellectual intelligence, and kinesthetic intelligence. However, in the practice of education in schools, until now there are indications that it is not serious, especially in efforts to develop students' spiritual and emotional intelligence. Even though the development of these two intelligences is an aspect that greatly determines the success of character education. Through a literature review, this paper seeks to reveal the urgency of teacher spiritual and emotional intelligence which is a key factor for students' character education efforts in schools. So that it can inspire each school and education policy makers in efforts to improve the quality of character education through increasing the spiritual and emotional intelligence of teachers.